The language of the GDPR: translation issues and archival issues in four non-English-speaking countries - Foscarini , Fiorella; Barrera , Giulia; Škoro Babić , Aida; Henttonen , Pekka; Gunnlaugsdóttir , Jóhanna (Archives & Manuscripts, 2021)
This article examines how key archival terms and concepts included in the General Data Protection Regulation (GDPR) have been translated into Italian, Slovenian, Finnish, and Icelandic languages. The study identifies a number of translation issues in each language, and reflects on the reasons for such mistakes and their impact on the archival practices affected. Mistranslations appear to be related to insufficient investigations of specific, local uses of archival terminology on the part of the translators, lack of involvement of archival professionals in the process of translation, and problems with the interpretation of the legal system and the archival traditions involved.